Study of the phase-evolution mechanism of an Fe-Se system at the nanoscale: optimization of synthesis conditions for the isolation of pure phases and their controlled growth - Ghalawat, Monika; Poddar, Pankaj (Langmuir, 2020)
The iron selenide (Fe-Se) family of nanoparticles (FexSey-where x/y ranges from 1:2 to 1:1) has been fabricated by a thermal decomposition method. The control over solution chemistry has been developed by intensively investigating the effect of reaction parameters by means of wide-angle X-ray scattering, leading to the rich insights into the phase-evolution mechanism of the Fe-Se system. The phase transformation followed the FeSe2 -> Fe3Se4 -> Fe7Se8 -> FeSe sequence in the temperature range of 110-300 degrees C. The deep mechanistic insight helped in the identification of optimized conditions needed to crystallize the individual phase of the Fe-Se system as well as control of the morphology, crystalline phase purity, and thermal stability of the obtained Fe-Se nanoparticles.